STRUCTURE AND COMPRESSIBILITY OF SYNTHETIC ZNAL2O4 (GAHNITE) UNDER HIGH-PRESSURE CONDITIONS, FROM SYNCHROTRON X-RAY POWDER DIFFRACTION - Levy D.; Pavese A.; Sani A.; Pischedda V. (My University, 2001)
The structural behavior of synthetic gahnite (ZnAl2O4) has been investigated by X-ray powder diffraction at high pressure (0–43 GPa) and room temperature, on the ID9 beamline at ESRF. The equation of state of gahnite has been derived using the models of Birch–Murnaghan, Vinet and Poirier–Tarantola, and the results have been mutually compared (the elastic bulk modulus and its derivatives versus P determined by the third-order Birch–Murnaghan equation of state are K0=201.7(±0.9) GPa, K ′0=7.62(±0.09) and K ″0=−0.1022 GPa−1 (implied value). The compressibilities of the tetrahedral and octahedral bond lengths [0.00188(8) and 0.00142(5) GPa−1 at P=0, respectively], and the␣polyhedral volume compressibilities of the four-␣and␣sixfold coordination sites [0.0057(2) and 0.0041(2) GPa−1 at P=0, respectively] are discussed.
Keywords: SYNTHETIC-GAHNITE; STRUCTURAL BEHAVIOUR AT HP; EOS